METHODS AND MODELS OF RESEARCH OF INVESTMENT ATTRACTIVENESS AND COMPETITIVENESS OF PROJECT-ORIENTED ENTERPRISE IN THE PROCESS OF CREATING INNOVATIVE HIGH-TECH - Oleg Fedorovich; Viktor Kosenko; Liudmyla Lutai; Iaroslav Zamirets (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the research is the investment attractiveness of enterprises producing competitive products with modern component architecture. The aim of the article is to develop complex methods for research of investment attractiveness of projects on creation of new high-tech products with component architecture. Tasks to be solved are: to use component method for the analysis of innovativeness of created high-tech products; to study investment attractiveness of an innovation project with the use of expert assessments and the method of planning experiments; to substantiate the composition of a diversification project portfolio for investment taking into account the limited possibilities of the enterprise based on the method of integer optimization; to study the performance of the project portfolio using agent-based imitational modeling. Methods used are: system analysis, component design, multi-criteria optimization, expert assessment and agent-based simulation modeling in the form of applied information technology. The results have been obtained: the analysis of investment attractiveness of projects on creation of new high-tech products with component architecture is carried out. The architecture of a complex product built with components from previous positive development experience is investigated. A classification of possible components in the architecture of a complex product is created. A set of indicators for assessing the investment attractiveness of an innovative component-based product is formed. The qualitative assessments of experts for the main indicators of the component composition of the product in the form of linguistic variables are proposed. The use of multifactor experiment to assess the investment attractiveness of a project to create a complex product with a component-based architecture is proposed. An optimization model for selecting the rational composition of components in an innovative product is developed. An agent-based simulation model is built to study the performance of work on the preparation of production of innovative products on a component basis. Conclusions: The use of a set of developed methods and applied information technology for the creation of high-tech products with component-based architecture allows you to plan a diversification portfolio of projects with investment attractiveness and competitiveness of products.